The results of entomological monitoring West Nile fever on the territory of the Crimean peninsula in the 2022 season - N. A. Zarubin; N. V. Borodai; S. K. Udovichenko; A. Yu. Galkina; I. D. Kaysarov (Медицинский вестник Юга России, 2024)
Objective: to evaluate the role of blood-sucking mosquitoes of various species living in the northern and central regions of the Crimean Peninsula in the transmission of West Nile virus (WNV).Materials and methods: the collection of bloodsucking mosquitoes was carried out in 7 administrative units of the Republic of Crimea with automatic traps and a vertical handheld vacuum cleaner from July 1 to August 5, 2022. The species composition of mosquitoes was determined visually using an MSP-1 stereomicroscope (option 22) using standard keys. Detection of WNV RNA in the samples was performed by RT-PCR. Mosquito infection levels and dominance index were calculated.Results: a common eudominant species for urban and rural biotopes of the surveyed areas was determined Ae. caspius, whose dominance index was 72.4% and 31.3%. Mosquitoes of the species Cx. modestus were the most numerous in rural biotopes (dominance index — 48.4%). The invasive species Ae. albopictus in the central part of the Crimean peninsula, which indicates the expansion of its habitat. Of 18.6 thousand mosquitoes of 12 species, merged in 693 samples, WNV RNA was detected in 14 samples (2.02%), 3 isolates of the pathogen were isolated. A high level of WNV infection of mosquitoes in urban biotopes was established, which amounted to 4.12%. WNV circulation was first confirmed in the northern part of Crimea (Krasnoperekopsky district).Conclusion: the epidemiological significance of mosquitoes of various species on the territory of the Crimean Peninsula has been determined. The data on the spread of WNV in the Republic of Crimea were supplemented, taking into account which the estimated zoning of the territory was carried out according to the degree of risk of infection with WNV. Recommendations are given to strengthen epidemiological surveillance and preventive measures.